Unilateral and Bilateral Adrenalectomy for Pheochromocytoma Requires Adjustment of Urinary and Plasma Metanephrine Reference Ranges - Osinga, Thamara E.; van den Eijnden, Maartje H. A.; Kema, Ido P.; Kerstens, Michiel N.; Dullaart, Robin P. F.; de Jong, Wilhelmina H. A.; Sluiter, Wim J.; Links, Thera P.; van der Horst-Schrivers, Anouk N. A. (The journal of clinical endocrinology and metabolism, 2013)
Context:Follow-up after adrenalectomy for pheochromocytoma is recommended because of a recurrence risk. During follow-up, plasma and/or urinary metanephrine (MN) and normetanephrine (NMN) are interpreted using reference ranges obtained in healthy subjects.Objective:Because adrenalectomy may decrease epinephrine production, we compared MN and NMN concentrations in patients after adrenalectomy to concentrations in a healthy reference population.Design:A single-center cohort study was performed in pheochromocytoma patients after adrenalectomy between 1980 and 2011.Subjects:Seventy patients after unilateral and 24 after bilateral adrenalectomy were included.Main Outcome Measures:Plasma-free and urinary-deconjugated MN and NMN determined at 3 to 6 months and annually until 5 years after adrenalectomy were compared with concentrations in a reference population. Data are presented in median (interquartile range).Results:Urinary and plasma MN concentrations 3 to 6 months after unilateral adrenalectomy were lower compared with the reference population (39 [31–53] μmol/mol creatinine and 0.14 [0.09–0.18] nmol/L vs 61 [49–74] μmol/mol creatinine and 0.18 [0.13–0.23] nmol/L, respectively, both P < .05). Urinary MN after bilateral adrenalectomy was reduced even further (7 [1–22] μmol/mol creatinine; P < .05). Urinary and plasma NMN were higher after unilateral adrenalectomy (151 [117–189] μmol/mol creatinine and 0.78 [0.59–1.00] nmol/L vs 114 [98–176] μmol/mol creatinine and 0.53 [0.41–0.70] nmol/L; both P < .05). Urinary NMN after bilateral adrenalectomy was higher (177 [106–238] μmol/mol creatinine; P < .05). Changes in urinary and plasma MNs persisted during follow-up.Conclusion:Concentrations of MN are decreased, whereas NMN concentrations are increased after unilateral and bilateral adrenalectomy. Adjusted reference values for MN and NMN are needed in the postsurgical follow-up of pheochromocytoma patients.